VDSC steganalysis algorithm of echo hiding - YANG Yu1; LEI Min1; NIU Xin-xin1; YANG Yi-xian1 (Tongxin xuebao)
Based on the idea that echo hiding changing the cepstrum distribution of natural audio,a new audio steganaly-sis method was presented.The VDSC（variants of difference of sum of cepstrum）was constructed to decet echo hiding audio files without estimating the size of hiding fragment.Experiment results show the accuracy of detecting echo hiding audio files is 88%.